2019
DOI: 10.1088/1755-1315/353/1/012047
|View full text |Cite
|
Sign up to set email alerts
|

Acute Oral Toxicity Test of Nicotiana tabacum L. Bio-Oil Against Female Winstar Rats

Abstract: Tobacco plants are notably known for its pesticidal properties, particularly due to its nicotine content. In this study, Nicotiana tabacum L. bio-oil was obtained using pyrolysis technique. The safety of the bio-oil to be used as bioinsecticide was analyzed through acute oral toxicity test by administering 5000 mg bio-oil/kg body weight of female winstar rats that were analogous to humans. It was concluded that the bio-oil was not toxic due to absence of mortality and no significant change in the body weight a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…E. helioscopia was safe and produced no physiological alternations of vital organs and the biochemical parameters were also unchanged at the tested doses ( Saleem et al, 2016 ). S. anthelmia and N. tabacum did not affect the body weight and animal behavior and were considered to be non-toxic ( Ribeiro et al, 2017 ; Andjani et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…E. helioscopia was safe and produced no physiological alternations of vital organs and the biochemical parameters were also unchanged at the tested doses ( Saleem et al, 2016 ). S. anthelmia and N. tabacum did not affect the body weight and animal behavior and were considered to be non-toxic ( Ribeiro et al, 2017 ; Andjani et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The leaf part of Artemisia afra , Azadirachta indica , Brucea antidysenterica , Buddleja polystachya , Eucalyptus Globulus , Gloriosa superba , Maytenus heterophylla , Nicotiana tabacum , and Ocimum lamiifolium are commonly used for the preparation of remedies used to treat epilepsy and related symptoms in Ethiopia. The acute toxicity studies conducted in the crude extracts, essential oils and bio-oils recapped the absence of gross behavioral, physical changes and signs of overt toxicity such as lacrimation, urination, muscle weakness and convulsions in different animal models [ 175 – 181 ]. As depicted in Table 5 , relatively higher LD 50 value greater than 5000 mg/kg of body weight were recorded for Artemisia afra , Azadirachta indica , Gloriosa superba , and Nicotiana tabacum extracts.…”
Section: Pharmacological Evidence Of Reported Medicinal Plantsmentioning
confidence: 99%
“…In addition, the stem extract caused pronounced toxicity at 1200 mg/kg [ 180 ] 27 Myrica salicifolia R HME Non-pregnant female mice 2000 > 2000 There are no visible signs of overt toxicity and mortality in mice treated with the extract at 2000 mg/kg [ 211 ] 28 Nicotiana tabacum L Bio-oil Female Wistar rats (130–140 g) 5000 > 5000 The rats exhibited no significant change in the body weight and behavior. In addition, there was no mortality of rats in the study period [ 181 ] 29 Ocimum lamiifolium L ME Swiss albino mice (27–36 g) 500, 1000 & 2000 ≥ 2000 The crude extract didn’t trigger gross visible signs of acute toxicity such as urination, hair erection, lacrimation, and reduction in feeding activity [ 194 ] 30 Olea europaea L ET Wistar rats of either sex (150–200 g) 2000 ≥ 2000 Oral administration of the extract didn’t cause any mortality or sign of toxicity at 2000 mg/kg of body weight during the study period [ 212 ] 31 Opuntia ficus-indica S HET White Sprague Dawley rats either sex 500, 1000 & 2000 The rats exhibited no genotoxicity at all treatments regimens even at the maximum dose of 2000 mg/kg [ …”
Section: Pharmacological Evidence Of Reported Medicinal Plantsmentioning
confidence: 99%
“…Furthermore, nicotine was assigned as a botanical insecticide with dissipation half-live of 2.51 days, thus making it readily dissipated from treated plants [45]. In addition, acute oral toxicity test showed that 5 g Nicotiana Tabacum L. bio-oil, with nicotine as the most dominant compound, per kg body weight of female Wistar rats was not toxic due to the absence of mortality and no significant change of the body weight and behavior of the rats [46]. It could be concluded that besides its far below toxicity level to humans and animals, the EHRE-Nt shows highly potential bioinsecticidal activity.…”
Section: E Intensity Of Cbbs Attackmentioning
confidence: 99%